Cambridge IGCSE English as a Second Language - Reynolds, John (London Hodder Education, 2017)
The easiest and most cost effective way to teach both the speaking and listening components
Include Color Illustration and Index
Keywords: English language -- English language--Study and teaching--Foreign speakers